Validation of the 18-gene classifier as a prognostic biomarker of distant metastasis in breast cancer. - Skye Hung-Chun Cheng; Tzu-Ting Huang; Yu-Hao Cheng; Tee Benita Kiat Tan; Chen-Fang Horng; Yong Alison Wang; Nicholas Shannon Brian; Li-Sun Shih; Ben-Long Yu (PLoS ONE)
We validated an 18-gene classifier (GC) initially developed to predict local/regional recurrence after mastectomy in estimating distant metastasis risk. The 18-gene scoring algorithm defines scores as: <21, low risk; ≥21, high risk. Six hundred eighty-three patients with primary operable breast cancer and fresh frozen tumor tissues available were included. The primary outcome was the 5-year probability of freedom from distant metastasis (DMFP). Two external datasets were used to test the predictive accuracy of 18-GC. The 5-year rates of DMFP for patients classified as low-risk (n = 146, 21.7%) and high-risk (n = 537, 78.6%) were 96.2% (95% CI, 91.1%-98.8%) and 80.9% (74.6%-81.9%), respectively (median follow-up interval, 71.8 months). The 5-year rates of DMFP of the low-risk group in stage I (n = 62, 35.6%), stage II (n = 66, 20.1%), and stage III (n = 18, 10.3%) were 100%, 94.2% (78.5%-98.5%), and 90.9% (50.8%-98.7%), respectively. Multivariate analysis revealed that 18-GC is an independent prognostic factor of distant metastasis (adjusted hazard ratio, 5.1; 95% CI, 1.8-14.1; p = 0.0017) for scores of ≥21. External validation showed that the 5-year rate of DMFP in the low- and high-risk patients was 94.1% (82.9%-100%) and 80.3% (70.7%-89.9%, p = 0.06) in a Singapore dataset, and 89.5% (81.9%-94.1%) and 73.6% (67.2%-79.0%, p = 0.0039) in the GEO-GSE20685 dataset, respectively. In conclusion, 18-GC is a viable prognostic biomarker for breast cancer to estimate distant metastasis risk.